Development of a Quinquennial Journal Roadmap and Presentation of Sexennial Research Publication Metrics of an Asian Journal - C. Orlanda-Ventayen, Caren (Asian Journal of Multidisciplinary Studies, 2023)
As the incoming Editor-in-Chief (EIC) of the Asian Journal of Multidisciplinary Studies, it is essential to conduct a study focused on improving current journal. This study aims to analyze the journal's publication metrics from 2018 to 2023 (quinquennial), providing a review of key indicators such as the number of articles published, view rates, and other relevant data from external sources such as Google Scholar. By evaluating these metrics, the study offers insights into the journal's performance and growth trends over the past six years. These findings will serve as the foundation for developing a strategic roadmap for the journal from 2025 to 2029 (quinquennial). The roadmap will focus on improving publication standards, expanding the journal’s reach, and enhancing its scholarly impact. The study will contribute to the evolving academic landscape and the journal’s long-term goals. This forward-looking approach will guide the journal's development, aiming to position it as a leading platform for multidisciplinary research in Asia and beyond.